2010
DOI: 10.1002/jctb.2372
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biosynthesis of alginates

Abstract: Alginates are polysaccharides with many industrial and medical uses, from food additives to encapsulation agents in the emerging transplantation technologies. Alginate is composed of variable proportions of β-D-mannuronic acid and α-Lguluronic acid linked by 1-4 glycosidic bonds. Traditionally, commercial alginate has been produced by farmed brown seaweeds, but this alginate suffers from heterogeneity in composition and quality partly due to environmental variation. Two bacterial genera, Pseudomonas and Azotob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(81 citation statements)
references
References 108 publications
0
77
0
Order By: Relevance
“…The yield of EPS increases when the biomass production decreases. And also the specific yields of EPS production were higher as the initial concentration of substrates increased (Hay et al, 2010). From these studies, three Azotobacter strains viz., AztRMD2, AztPMK1 and AztPMK2 were selected for further experiments.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The yield of EPS increases when the biomass production decreases. And also the specific yields of EPS production were higher as the initial concentration of substrates increased (Hay et al, 2010). From these studies, three Azotobacter strains viz., AztRMD2, AztPMK1 and AztPMK2 were selected for further experiments.…”
Section: Resultsmentioning
confidence: 80%
“…The EPS of Azotobacter are copolyuronans ubiquitous nature of alginates (Elsayed et al, 2013) commercially used in plant tissue culture to produce insoluble artificial seeds, immobilizing enzymes by entrapment, as food and wound dressing substances. Thus the industrial application of alginate is well understood (Hay et al, 2010). Aside from industrial application, Azotobacter alginate plays a key role in encystment, to provide protection against desiccation and predation by protozoa or phage attack (Hynes et al, 2008), or affect the penetration of antimicrobial agents and toxic metals (Aleem et al, 2003).…”
Section: Issn: 2319-7706 Volume 6 Number 6 (2017) Pp 2310-2320mentioning
confidence: 99%
“…Those gene encodes for phosphomannomutase involved in rhamnolipid and lipopolysaccharide biosynthesis. Operon was containing all the genes that encode proteins involved in the biosynthesis of alginate (algD and algae for precursor synthesis, algl, algJ, and algF for acetylation, algG to epimerisasi, algL for degradation) (Hay et al 2010). The potent isolates CRB 19 and CR 90 exhibited the highest activity of EPS secretion and based on 16S rRNA analysis revealed CRB 19 and CR 90 belonged to P. aeruginosa strain B2 and Brevibacillus brevis B33, respectively Other studies showed that those group was known as promoting growth in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Role of different exopolysaccharide encoding genes has been confirmed previously in various lactic acid bacteriaat genus and species level (Broadbent et al, 2003;Jolly et al, 2001van Kranenburg et al, 1997). Generally microorganisms produce number of substances as a mixture of polymers which are synthesized through specific genes located on gene cluster (Hay et al, 2010;Orr et al, 2009;van Kranenburg et al, 1999). Although vast majority of genetic information is available on xanthan, related information on other types of exopolysaccharides is rare.…”
Section: Genetics and Biological Synthesis Of Exopolysaccharidein Lacmentioning
confidence: 96%
“…In addition, gum genes (D, H, I, K, M) also encode the biosynthesis of glycosyltransterase Vorholter et al, 2008). Recently it has been reported that in Pseudomonas aeruginosa, 12 gene cluster in a single operon encodes the production of alginates (Hay et al, 2010). However, a gum gene (algC) involved in EPS production was found to locate on chromosomal region which encodes phosphomannomutase (Hay et al, 2010).…”
Section: Genetics and Biological Synthesis Of Exopolysaccharidein Lacmentioning
confidence: 99%